Doughnut strikes sandwich: the geometry of hot medium in accreting black hole X-ray binaries - Juri Poutanen; Alexandra Veledina; Andrzej A. Zdziarski (EDP SCIENCES S A, 2022)
We study the effects of the mutual interaction of hot plasma and cold medium in black hole binaries in their hard spectral state. We consider a number of different geometries. In contrast to previous theoretical studies, we use a modern energy-conserving code for reflection and reprocessing from cold media. We show that a static corona above an accretion disc extending to the innermost stable circular orbit produces spectra not compatible with those observed. They are either too soft or require a much higher disc ionization than that observed. This conclusion confirms a number of previous findings, but disproves a recent study claiming an agreement of that model with observations. We show that the cold disc has to be truncated in order to agree with the observed spectral hardness. However, a cold disc truncated at a large radius and replaced by a hot flow produces spectra which are too hard if the only source of seed photons for Comptonization is the accretion disc. Our favourable geometry is a truncated disc coexisting with a hot plasma either overlapping with the disc or containing some cold matter within it, also including seed photons arising from cyclo-synchrotron emission of hybrid electrons, i.e. containing both thermal and non-thermal parts.